TEGAL BESAR BEACH REHABILITATION WITH SCALLOPED CONCRETE BLOCK REVETMENT - Pujianiki, Ni Nyoman (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021DO - 10.24843/JITS.2021.v25.i01.p09, 2021)
Klungkung has a coastline of 113 km out of a total of 5780.06 km 2 the coastline in the province of Bali, but about 25 km is eroded. One of the critical areas occurs in Tegal Besar beach which caused erosion of 0.08875 to 3.0915 m/yr. Revetment with scalloped concrete blocks is expected to protect land from the wave attack. Concrete blocks have uniform size and shape, showing the aesthetic aspect so as not damage the beauty of the beach. Analysis of wind, tidal, bathymetry and soil data are carried out to obtain the structure and stability of the revetment. The results of this design can be used to rehabilitate the condition of the Tegal Besar beach. From the analysis, the design wave height with a return period of 25 years (H 25 ) = 0.891 m, while the height with the breaking wave (Hb) = 1.003 m and the breaking wave depth (db) = 1.068 m and the design water level elevation (DWL) = 2.061 m calculated from MSL. The revetment structure has a height of 4.00 m, a peak width of 1.50 m, the weight of the first layer of protection is 300 kg and the second is 30 kg with a thickness of 1.00 m. Toe protection are 1.25 m high, 3.00 m wide and weigh 150 kg. The results showed that the revetment was stable against overturning, shearing, and the bearing capacity of the soil was declared safe with the results of overturning stability 22,075 > 2, slidding stability 2.249 > 1.5 and the bearing capacity of the soil 57,993 > 3 so that the revetment can be eligible to be applied at the site.